The Influence Of Sanitation, Cleanliness, And Facilities On Customer Satisfaction During Overnight Stays With Service Quality As A Mediating Variable At Hotel Grasia Semarang - Noor Faiq; Sapto Supriyanto (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This research was conducted at the Grasia Hotel Semarang which aims to analyze and explain the effect of sanitation and cleanliness and facilities which are in unfavorable conditions due to an increase and decrease in the occupancy rate of consumers staying from January 2022 to October 2022, and slow service to consumers when check-in, at the time of stay or in-house and at check out.Research data obtained through questionnaires and interviews. The sample used in the study had one hundred respondents. The research results are expected to provide useful information for management and teachers. The data obtained were processed using descriptive analysis and quantitative statistical analysis. Quantitative analysis uses multiple regression analysis to determine the effect of the independent variable on the dependent variable, test the model, test the hypothesis, and but before carrying out the test, the validity and reliability tests are carried out first.The results of the regression analysis show that the increase in consumer satisfaction is influenced directly or indirectly by sanitation, cleanliness, facilities, and quality of service. The results of the multiple regression analysis test showed a significant F value, with a determination correlation value of adjusted R2 square of 0.629. This shows that sanitation, facilities, and quality of service significantly affect consumer satisfaction while staying together with a close relationship of 62.9%. This shows that to increase consumer satisfaction, it is necessary to have sanitation, cleanliness, facilities, and good service quality.